Male parental care of Patagonian Crested Ducks Anas (Lophonetta) specularioides - Buitron, Deborah; Nuechterlein, Gary L (Wildfowl, 1989)
We observed the behaviour of Crested Ducks accompanying broods on small plateau lakes in southern Argentina. Time-budget data show that although females usually were closest to the brood, males were almost always nearby and spent more time alert than the females. Males were most active in both intraspecific and interspecific aggression. Both pair members took part in intraspecific aggression, and they cooperated closely in leading aggressive Upland Goose males away from their young. Both sexes, but especially males, used distraction displays. Our observations suggest that male Crested Ducks accompany broods to protect the ducklings, and that males play an important role in the care of ducklings from hatching to independence.